Rising powers in international conflict management: an introduction INTRODUCTION - PARLAR DAL, EMEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This introductory article sheds light on commonalities and divergences in a selected group of rising powers' (namely Brazil, India, China and Turkey) understanding and applications of conflict management and attempts to explain the priorities in their conflict management strategies from conceptual/theoretical and empirical aspects. The case studies in this special issue point to the evolving nature of conflict management policies of rising powers as a result of their changing priorities in foreign and security policy and the shifts observed in the international order since the end of the Cold War. The country specific perspectives provided in this issue have also proven right the potentialities of rising powers in managing conflicts, as well as their past and ongoing challenges in envisaging crises in both their own regions and extra-regional territories. The article begins by decoding the driving factors of rising powers' conflict management strategies and their commonalities and divergences in peacebuilding policies. It then jumps into the theoretical and conceptual assessment of their conflict management approaches. In the third part, the issue delves into the evidence-based assessment their converging and differing conflict management policies depending on the nature of the conflict, its involving actors and its geographical location.
Keywords: Rising powers; international conflict management; Brazil; China; Turkey; India